La motivación del personal en la corporación jarrín herrera agencia Babahoyo y su incidencia en el volumen de ventas - Castro Tacuri, Jessica Leticia (2017)
he present research work contains the writing of theoretical fragments of how a commercial enterprise is managed, which from the administrative and organizational point of view applies certain policies; that for this case we will make a study of the corporation Jarrín Herrera "Jaher" - Babahoyo agency; the same one that was founded in the city of Cuenca in 1989 by the young entrepreneur Don Alberto Jarrín Antón as a modest warehouse of household appliances and since 1996 forms a large national chain of 68 stores in 23 cities in the country as Cuenca , Quito, Sangolquí, Guayaquil, Durán, Milagro, La Troncal, Stata, Manta, Portoviejo, Ambato, Riobamba, Sto Domingo, Machala, Pasaje, Quevedo, Babahoyo, Ventanas, Montalvo, Guaranda, Puyo, Tena and Macas.